2021
DOI: 10.22219/procedia.v9i4.16346
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh token ekonomi untuk meningkatkan kemampuan rawat diri pada individu dengan gangguan skizoafektif

Abstract: The subject was a 41-year-old woman with a diagnosis of schizoaffective disorder. Subjects showed the symptoms of schizoid that made them less interested in daily activities, less concerned with hygiene and self-care. Assessment methods used are observations, interviews, and psychological tests in the form of WAIS, graphic tests (DAP, BAUM, &HTP), TAT, WWQ and WHODAS questionnaire. Interventions are made to deal with the lack of ability in self-care, using behavior modification therapy with the token econo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
1
0
1
Order By: Relevance
“…bahwa gangguan skizoafektif telah mewakili gejala-gejala yang ada dalam gangguan skizofrenia dan bipolar. Pasien yang menderita skizoafektif mengalami perubahan emosi yang kadang tidak terduga karena itu ia mudah sekali berubah menjadi tidak tertarik dengan aktivitas sehari-hari (Mintarsih, 2021). Pada kasus ini subjek memiliki permasalahan yang dialami yakni mondar-mandir.…”
Section: Pembahasanunclassified
“…bahwa gangguan skizoafektif telah mewakili gejala-gejala yang ada dalam gangguan skizofrenia dan bipolar. Pasien yang menderita skizoafektif mengalami perubahan emosi yang kadang tidak terduga karena itu ia mudah sekali berubah menjadi tidak tertarik dengan aktivitas sehari-hari (Mintarsih, 2021). Pada kasus ini subjek memiliki permasalahan yang dialami yakni mondar-mandir.…”
Section: Pembahasanunclassified
“…To establish a diagnosis of schizoaffective, an individual must show at least two weeks of positive psychotic symptoms followed by symptoms of a mood disorder such as mania or depression. If an individual experiences one of the symptoms of a mood disorder and meets the criteria for the disorder, it can be concluded that the person is schizoaffective (Mintarsih, 2021). In this case, the diagnosis was made based on a depressive condition as an initial symptom indicated by impulsive behaviour, namely a suicide attempt.…”
Section: Introductionmentioning
confidence: 99%